Mexico and the Spanish Civil War : political repercussions for the Republican cause - Ojeda Revah, Mario (Eastbourne : Sussex Academic Press, 2015)
"Based on first-hand diplomatic, political and journalistic sources, most unpublished, Mexico and the Spanish Civil War investigates the backing of the Second Republic by Mexico during the Spanish Civil War. Significant military, material and financial aid was given by the government of Lázaro Cárdenas (1934-1940) to the Republic, which involved not only direct sales of arms, but also smuggling operations covertly undertaken by Mexican diplomatic agents in order to circumvent the embargo imposed by the London Committee of Non Intervention. This path-breaking account reveals the operations in Spain of Mexican workers, soldiers, artists and intellectuals--such as later Nobel Laureate Octavio Paz and the Muralist David Alfaro Siqueiros--as volunteers and propagandists for the Republican cause. Engagement with the Spanish Civil War also had a profound impact upon Mexico's domestic politics as support for the Republic was equated by Cárdenas with his own revolutionary project"--Provided by publisher.
Spanish-Mexican relations, 1821-1931: an overview -- Relations with Republican Spain prior to the Civil War, 1931-1936 -- Material aid and diplomatic solidarity -- Arms for Republican Spain -- Volunteers and propagandists -- Domestic repercussions of the War -- The Republic's downfall and its effects on the Mexican revolution.
Includes bibliographical references (pages 263-278) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Cárdenas, Lázaro, -- 1895-1970.; Cárdenas, Lázaro, -- 1895-1970; Mexicans -- Spain -- History -- 20th century; Military assistance -- History -- 20th century; Economic assistance -- History -- 20th century; Mexico -- Foreign relations -- Spain; Spain -- Foreign relations -- Mexico; Mexico -- Military relations -- Spain; Spain -- Military relations -- Mexico; Spain -- History -- Civil War, 1936-1939 -- Participation, Mexican; Mexico -- Politics and government -- 1910-1946.; Mexicains -- Espagne -- Histoire -- 20e siècle.; Assistance militaire -- Histoire -- 20e siècle.; Aide économique -- Histoire -- 20e siècle.; Mexique -- Relations extérieures -- Espagne; Espagne -- Relations extérieures -- Mexique; Mexique -- Politique et gouvernement -- 1910-1946.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; Economic assistance; Mexicans; Military assistance; Military relations; Politics and government; Mexico; Spain; 1900-1999; History